EXISTENTIALISM IN ELEMENTARY EDUCATION: EFFORTS TO FOSTER SELF-AWARENESS AND RESPONSIBILITY AMONG STUDENTS AT SD MUHAMMADIYAH 36 MEDAN - Ambar Wulan Sari; Mahriyuni Mahriyuni; Khairun Niswa (Universitas Islam Negeri (UIN) Sumatera Utara, 2026)
This study aims to analyze the application of existentialist philosophical values in elementary education, particularly in efforts to foster self-awareness and responsibility among students at SD Muhammadiyah 36 Medan. Existentialist philosophy emphasizes individual freedom, self-awareness, and moral responsibility as the foundation for forming an authentic human existence. In the context of elementary education, these values are relevant for shaping students' character so they become aware of their existence and capable of taking responsibility for their actions. This research employs a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The research subjects include the principal, classroom teachers, and students of SD Muhammadiyah 36 Medan. The data were analyzed thematically through the processes of reduction, presentation, and conclusion drawing. The findings indicate that the application of existentialist values at SD Muhammadiyah 36 Medan is reflected in learning practices that provide freedom of thought, opportunities for expression, and self-reflection on learning experiences. Teachers act as facilitators who guide students to understand the meaning of freedom and responsibility in each learning activity. In addition, routine activities such as cleanliness duty, congregational prayer, and the Anak Mandiri (Independent Child) program strengthen the development of students' moral and social responsibility. The existentialist values in this school are also integrated with Islamic teachings, ensuring that individual freedom remains aligned with spiritual responsibility toward God. This study shows that education grounded in existentialist values can shape students to become authentic, reflective, faithful, and responsible individuals. The integration of existentialism and Islamic values in the Muhammadiyah educational context creates a humanistic and spiritual educational model, in line with the goal of forming holistic human beings.